Prototype Design of Event Chronological Information System to Support External Cause Coding of Emergency Room Patients - Tausiah, Ai Lia; Setiatin, Sali; Abdussalaam, Falaah (Journal of Scientific Insights, 2025)
Chronological records of events in the Emergency Department (IGD) are often unstructured, resulting in incomplete data and External Cause coding errors (ICD-10). This research aims to develop a prototype of a web-based information system to facilitate the chronological recording of events in a standardized manner, thereby improving the accuracy of codification. The development method uses the Waterfall model with the stages of needs analysis, design (context diagram, DFD, ERD), implementation (HTML, Bootstrap, Flask, SQLite), and Blackbox testing. As a result, the system provides a structured interface for the input of incident data (accidents, violence) and generates automated PDF reports that are ready for codefinition. Functional testing shows all modules (data inputs, filters, generated reports) are operating as expected. The system has the potential to reduce coding errors based on related literature studies, while supporting integration with Electronic Medical Record (EMR). Recommendations for advanced research include clinical trials and the development of artificial intelligence features for automated code recommendations.